TEKNIK PEMBUATAN PERANTI WILLIAMS EXPANDER PADA KASUS GIGI BERJEJAL ANTERIOR RAHANG BAWAH: LAPORAN KASUS - Najwa Artika Sari; Anisa Nur Halimah; Winda kusumawardani; Sianiwati Goenharto (Dentin, 2026)
Background: In the field of orthodontics, anterior dental crowding in the mandibular arch is a common problem that affects aesthetic appearance, masticatory function, and periodontal tissue health. This study focused on the development of a fixed Williams Expander appliance as a solution to overcome dental arch misalignment in the mandible. Objective: To determine the proper fabrication technique of the Williams Expander in cases of mandibular anterior dental crowding. Case: The laboratory received a working model with a case of anterior dental crowding in the early permanent dentition phase, and the dentist provided instructions for the fabrication of a fixed orthodontic appliance, namely the Williams Expander, to correct dental crowding and dental arch misalignment. The fabrication process of this fixed Williams Expander appliance utilized various instruments and materials, such as molar band s, which were used for anchorage and as a strong connection between the arms of the Hyrax screw and the molar band s. This fabrication process was carried out in stages, resulting in a stable and effective fixed Williams Expander appliance for creating space for overlapping teeth. Conclusion: The fabrication stages of this fixed Williams Expander appliance began with drawing the design, relieving the interdental area to a depth of 2–3 mm, adjusting the molar band s by cutting the lingual part of the molar band s and performing welding, fitting the screw according to the mandibular arch, soldering with the application of flux and antiflux, followed by finishing and polishing.Keywords : Anterior dental crowding, Fixed orthodontic appliance, Williams Expander.